Libia ante la Unión para el Mediterráneo: Realidades y Perspectivas - Uruburu Colsa , Manuel (Nómadas. Critical Journal of Social and Juridical Science, 2010)
After an evolution in his position, as the Project of the Union for the Mediterranean was acquiring its final shape, the libyan leader, Mu´ammar al-Gadafi issued a statement on 10 july 2008 announcing the reasons for which the government of his country rejected the inclusion of Libya within this new framework of regional cooperation. Further development of political events in this region and its reflection on the functioning of the Union for the Mediterranean appear to show the realism of some of the proposals put forward by Gaddafi to justify the decision of the Libyan government on the issue.
Keywords: Libya; Union for the Mediterranean; Regional cooperation